Analisis Yuridis Pelaksanaan Rahasia Bank dalam Tindak Pidana Pencucian Uang - Muhammad Amin; Lilik Prihatin; Bayusakti Yudhopramudyo (LPPM Universitas Ekasakti Padang, 2024)
The legal consequences of bank secrecy in money laundering crimes in Indonesia are examined in this research. While bank secrecy is an important tool for maintaining consumer trust, efforts to reduce money laundering may face resistance. By using normative research techniques as well as conceptual and legislative approaches, this research assesses the effectiveness and impact of bank secrecy laws in money laundering crimes. The findings of this study indicate that although bank secrecy is critical to maintaining public confidence in the banking system, this importance must be balanced with the need for strong law enforcement measures to combat money laundering.